Development and application of metallic dampers in bridge engineering: A review - Wenxi Wang; Sheng Chen; Bei Chen; Guokun Liu; Xugang Hua; Zhengqing Chen (Journal of Traffic and Transportation Engineering (English ed. Online))
Bridges may suffer from large-amplitude vibrations due to strong winds, earthquakes, human-induced loads, and vehicle-induced dynamic loads. Metallic dampers employed the energy dissipation from the hysteretic behavior of metal materials are among the most effective methods to mitigate bridge vibrations. This paper reviews the development and application of metallic-yielding dampers for the vibration control of bridges. Various theoretical models for metallic damper analyses are reviewed. Different yielding mechanisms and manufacturing materials of metallic dampers are discussed. Finally, the recent progress and application of bridge engineering are summarized. It can be concluded that each section of the torsion-type metallic damper exhibits a uniform stress state and undergoes plastic deformation simultaneously. Therefore, the damper has a strong energy dissipation capacity. Additionally, self-centering metallic dampers can automatically recover to their initial position after suffering an earthquake. Combined metallic dampers can take advantage of different types of dampers, thereby enhancing damping performance. Finally, these dampers will significantly enhance the seismic performance and overall safety of bridge structures. Future research will likely focus on hybrid systems that combine metallic dampers with other energy consumption mechanisms to further improve adaptability and energy dissipation, advancing the resilience and safety of bridge structures.